2014
DOI: 10.2478/afmnai-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Early Postoperative Complications after Surgery for Crohn's Disease

Abstract: The aim of this study was to show the influence of various risk factors on early postoperative complications following surgery for Crohn's disease (CD). In this review, an online internet database was searched, and also systematic review of the literature was performed. Three different studies from different countries were analyzed and compared with the results obtained in our University Clinic of Digestive Surgery -Skopje. The first review shows the influence of positive resection margins in CD on septical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Yamamoto et al retrospectively analyses 343 patients underwent intestinal anastomosis operations and found that an albumin level less than 30 g/L was an independent risk factor for IASCs [ 9 ]. However, there are also several studies failed to find out the significant correlation between albumin level and the happening of IASCs [ 11 , 21 , 22 ]. Therefore, the relationship between albumin level and postoperative IASCs remains controversial and data from Chinese patients with CD are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamamoto et al retrospectively analyses 343 patients underwent intestinal anastomosis operations and found that an albumin level less than 30 g/L was an independent risk factor for IASCs [ 9 ]. However, there are also several studies failed to find out the significant correlation between albumin level and the happening of IASCs [ 11 , 21 , 22 ]. Therefore, the relationship between albumin level and postoperative IASCs remains controversial and data from Chinese patients with CD are limited.…”
Section: Discussionmentioning
confidence: 99%
“…The serum albumin measurement is convenient and inexpensive [ 20 ], which makes it a potential candidate for practical predictive index. Although several studies have indicated the possible correlation between albumin level and the risk for IASCs, data from Asian population is scare and controversial [ 11 , 21 , 22 ]. Therefore, we designed this study, aiming to evaluate the impact of preoperative hypoalbuminemia on the development of IASCs after primary anastomosis for CD.…”
Section: Introductionmentioning
confidence: 99%